Endovascular treatment of a mycotic aneurysm in an immunocompromised child with acute leukemia—case report and review of the literature - Diepenbruck, Sabine Daphne; Jakob, Andre; Haas, Nikolaus Alexander; Mandilaras, Guido (Frontiers in Pediatrics, 2023)
Mycotic aneurysms are dilatations of an artery, a rare but severe complication due to infectious obliteration of the vessel wall. Thoracic aneurysms often present with unspecific symptoms and display multiple diagnostic and therapeutic challenges. In an advanced state they have an increased risk of perforation and a high mortality rate. The surgical therapeutic approach has a high perioperative complication rate. We introduce a case of a thoracic mycotic aortic aneurysm in an immunocompromised pediatric patient caused by Klebsiella pneumoniae bacteremia. A combination of prompt antibacterial treatment and minimally invasive stent implantation showed a good outcome evading the possible severe surgical problems.